Origin and evolution of microgranular enclaves hosted in the Cambrian granitoids of Champawat region, Kumaun Lesser Himalaya, India - Kumar S.; Singh B.N.; Castro A.; Pundir S.; Panwar K.S. (My University, 2025)
Felsic magmatism in the Champawat and adjoining regions of Kumaun Lesser Himalaya, referred herein as Champawat granitoids (CG), represents one of the Cambro-Ordovician (500±25 Ma) granitoid plutons of Lesser Himalayan Belt. The microgranular enclaves (ME) hosted in CG exhibit features of crystal-charged mafic-felsic magma mixing (hybrid), mingling and undercooling into relatively cooler and crystallizing host granitoid magma. The ME are metaluminous to peraluminous (molar Al2O3/CaO+Na2O+K2O=0.98-1.26) in the silica range of 58.39-68.27 wt.%, whereas CG are mildly to strongly peraluminous (molar Al2O3/CaO+Na2O+K2O=1.04-1.37) in the silica range of 62.97-70.77 wt%, t both belonging to calc-alkaline magma series. Al2O3, Fe2O3, MnO, MgO, CaO, V, Co, Ga, and Rb show linear variation trends with increasing silica due to mixing-fractionation of coeval mafic-felsic magmas. The ME magma probably formed t from mantle source as indicated by enriched Fe2O3, TiO2, MgO, Nb, Y, Ga, V, Cr, Co, and Ni whereas CG parental melt is sourced from lower crust amphibolite. The normalized elemental patterns of ME-CG pairs most probably suggest differential degrees of chemical re-equilibration between them. Mafic to hybrid (ME) magma once injected into cooler granitoid melt, have started experiencing physical and chemical changes depending upon ME size and resident time of its semi-solid condition, before the entire ME-CG magma system solidified. These processes may have also occurred within the conduits during magma ascent. The ME and CG appear to have originated and evolved in syn-to post-collisional environments during the assembly and growth of Gondwanaland. © 2022, Wadia Institute of Himalayan Geology. All rights reserved.